DEVELOPMENT OF RARA STORYTELLING APPLICATION-BASED INTERACTIVE LEARNING MEDIA TO TRAIN STORY-LISTENING SKILLS - Wulandari, Wisla; Yuliana, Rina; Tisnasari, Sundawati (Department of Primary education, Faculty of Teacher Training and Education, Universitas Su, 2022)
AbstractListening ability in elementary school is still relatively low. This is due to several factors, such as the use of attractive learning media is still rare, so the development of interactive learning media is needed. This development aims to produce interactive learning media based on the Rara Storytelling application and to determine the feasibility and response of students regarding the developed media. The research method used is research and development (R&D) using the Borg and Gall model modified by Sugiyono from stages one to six. The subjects were 31 students of 4th grade B at SDN Banjar Agung 1. The results of this research indicate that interactive learning media based on the Rara Storytelling application are “very feasible